Optimising adolescents and young adults’ utilisation of sexual and reproductive health and HIV services in Chad: a sensemaking approach - Rifat Atun; Aisha Yousafzai; Esias Bedingar; Ngarossorang Bedingar; Ferdinan Paningar; Eric Mbaidoum; Naortangar Ngaradoum (BMJ Global Health)
Background Adolescents and young adults (AYA) aged 15–24 years account for nearly half of all new HIV infections globally, with over 80% residing in sub-Saharan Africa, where AIDS is a leading cause of death. In Chad, HIV/AIDS significantly impacts AYA, despite a reduction in national prevalence from 1.6% in 2010 to 1.0% in 2022. AYA still contribute to 26.3% of new infections, with young women facing four times the risk compared with young men. Barriers throughout the care continuum, including transitions from paediatric to adult services, contribute to an overall antiretroviral therapy (ART) coverage of 47% in 2023, with only 27% of males compared with 58% of females receiving treatment. These challenges impact access to sexual and reproductive health services and effective help-seeking.Methods This study used participatory action research with a sensemaking theoretical lens. From December 2021 to March 2024, data were collected from 52 AYA (aged 15–24, both HIV-positive and HIV-negative) in focus group discussions. Data were analysed using a modified grounded theory approach, with coding and category development guided by the constant comparison method.Results Findings indicate that empowering AYA in health decision-making requires an adaptable approach considering individual experiences, interpersonal influences and systemic factors. Such an approach can enhance engagement with healthcare services, increase service utilisation and treatment adherence and inform policy redesign for more effective service delivery.Conclusion This study advances the understanding of sensemaking in healthcare, illustrating how AYA in Chad navigate and interpret the healthcare system. It highlights the need for AYA-friendly services that foster clear communication, trust and responsive care. Strengthening health systems through adolescent-responsive policies, workforce training and decentralised service delivery can enhance AYA engagement, service utilisation and retention in care. Aligning services with AYA perspectives through community-driven approaches and system reforms can improve healthcare accessibility and outcomes in similar contexts.